Development of Tourism in a Competitive and Socio-Cultural Environment - SAVITSKAYA, Yulia P.; SKOK, Nataliya I.; FOMICHEV, Igor Yu. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).06, 2019)
Tourism development directly affects territorial biological diversity. Therefore, the main objective of this study is to analyze the biological diversity in the areas with intensive impact of tourism and recreational activities in the Altai Republic. The article presents the results of field studies in the Katun Nature Reserve in the Altai Republic. This territory is characterized by an excessive tourism and recreational burden on ecosystems. Based on the quantitative analysis, data on the abundance (density) of species of clavaceous lepidoptera (diurnal butterflies) and orthopterans, amphibians, reptiles, birds, small mammals, resources of superterraneous biomass of herbage cover and earthworms (lumbricidae) were obtained. The proposed publication is an attempt of a comprehensive analysis of changes occurring in biological communities as a result of the impact of tourism and recreational environmental management.